American economic growth : an economist's history of the United States - Davis, Lance E. (New York : Harper & Row, 1972)
The book deals with the history of economic growth and the changing conditions behind it ,using categories and theories that economists have developed for such study
Includes bibliographical references and index.
obn 22/01/2019
Loans
Keywords: United States--Economic conditions; Economic history; United States